Sequential fishways reconnect a coastal river reflecting restored migratory pathways for an entire fish community. Issue 2 (8th October 2018) - Rourke, Meaghan L.; Robinson, Wayne; Baumgartner, Lee J.; Doyle, Jonathon; Growns, Ivor; Thiem, Jason D.
Abstract : River regulation infrastructure has been implicated in worldwide aquatic biodiversity loss. In‐stream barriers such as weirs prevent fish migration and the impact can be particularly severe for diadromous species. Fishways are frequently installed on in‐stream barriers to reconnect migratory pathways and rehabilitate diadromous fish populations. Sequential fishways may be necessary in rivers where multiple barriers prevent migration. We monitored a coastal fish community's response to fish passage restoration at 10 predominantly low‐level weirs in the freshwater reaches of the Nepean River in southeastern Australia. Few studies have simultaneously assessed fish community passage at successive fishways within a river system. Prior to the installation of the fishways, there was a gradient of reduced species diversity in an upstream direction including the absence of many diadromous species, despite the regular inundation frequency of most weirs. Following the installation of the fishways, species diversity was still greater in the downstream monitoring sites; however, there was evidence of a positive change in fish community structure in middle and upstream sites. Most notably, three diadromous species rapidly expanded their distribution upstream and one amphidromous species expanded its downstream distribution. This study demonstrates appropriately designed successive fishways can successfully reconnect river systems for an entire fish community, encompassing species with a broad range of swimming abilities and diverse life histories.